Digital Literacy, Culture, and Engagement as Catalysts of SME Performance: Evidence from West Java - Lusiah Lusiah; Hartanti Nugrahaningsih; Ahmad Shalahuddin (Universitas Bangka Belitung, 2025)
Small and Medium Enterprises (SMEs) in West Java have lots of challenges in the digital era, and requirement of change which is most important to survive in new competitive environment. This research focuses on the identification of factors that affect the Business Performance of SMEs in the region. Applying Partial Least Squares analysis, this research investigates the research gap around Digital Literacy, Engagement in Digital Initiatives, Internal Digital Culture, Government Support Policies, and Market Competitiveness. An exploration of the relationship between the variables of Digital literacy, Digital engagement, and digital culture and their effect on SMEs business performance show that research tests point to significant effects of the three variables on at least one dimension of Business performance. Nonetheless, Government Support Policies and Market Competitiveness appear to be less relevant but they still have places. There is evidence where governments have provided chances to SMEs, though not optimal. In this sporting goods industry, market forces justified the business need for adaptation in today’s market. This research provides valuable recommendations to policy makers and practitioners. When digital challenges are understood as unavoidable obstacles and approached as a set of priorities, getting to know internal digital cultures, economies, and financing opportunities in the context of West Java SMEs, it will be possible to outline general strategies for the successful development of firms in the discussed region.